An investigation into structural behaviors of skulls chewing food in different occlusal relationships using FEM - Hee‐Sun Kim; Jae‐Yong Park; Yeo‐Kyeong Lee; Youn‐Sic Chun (Wiley, 2020)
Abstract Objectives This study aims to investigate the effect of different occlusal relationships on skull structural and mechanical behaviors through simulation of chewing food. Methods Finite element (FE) skull models of occlusion for Class I, end‐on Class II, and full‐cusp Class II were generated. End‐on Class II and full‐cusp Class II were chosen as mild and severe Class II occlusions, respectively. A simplified food bolus was introduced between the upper and lower dentition of the right molars. Chewing food was simulated in the skulls by moving the mandible. An experiment was conducted to measure strains at selective locations and compared them to the analytical results for validation. Results In the early stages of mandibular movement, masticatory forces predicted from the skull models without food were lower than the skull models with food but increased drastically after occluding teeth full enough. As a result, the relationship between masticatory force and mandible movement shows that there is no significant difference between the skull models with food and without food in the range of human masticatory force, approximately 250 N. In all the cases of skulls including a food bolus, stress was similarly propagated from the mandible to the maxilla and concentrated in the same regions, including the mandibular notch and alveolar bone around the lower molars. Conclusion It is predicted that there is no significant difference of bite force-mandible movement relationships and stress distributions of skull and teeth, between end‐on Class II and full‐cusp Class II models. When simulating chewing activities on candy and carrot, it is also found that there is no difference of masticatory performance between Class II occlusions, from structural as well as mechanical perspectives.